Evidences on Price Discovery in BRICS - Sharma, Prashant; Arora, Geetika; Gupta, Prashant (International Journal of Economics and Financial Issues, 2020)
The present study tries to assess the price discovery process in BRICS economies. The price discovery is tested by assessing the long run and short run causality between the future and spot market indices of BRICS economies. The study employs daily closing prices of spot and future indices of BRICS economies. After testing the stationarity and order of integration of spot and future market series, the study employs Johansen co-integration test to assess the long run co-integrating relationship between the two markets. The long run causality is tested using error correction mechanism and Wald test is used to assess the short run causality. The results of the study suggest that the price discovery process is taking place in case of Russia and China in long run. The short run causality exists between future and spot market in case of Brazil and Russia. Keywords: Price discovery, Johansen co-integration, Error correction mechanism, BRICS JEL Classifications: C2, E3 DOI: https://doi.org/10.32479/ijefi.10238